Internet-Based chat support groups for parents in family-based treatment for adolescent eating disorders: a pilot study - Binford Hopf, Roslyn B.; Moessner, Markus; Bauer, Stephanie (European eating disorders review, 2013)
Objective This study aims to examine the feasibility and acceptability of an Internet-based chat support group for parents implementing family-based treatment (FBT). Method Participants (N = 13) were parents of adolescents with eating disorder who participated in 15 weekly online therapist-guided chat sessions. Sessions focused on encouraging and supporting parental efforts to help their child overcome an eating disorder. Results Chat programme satisfaction ratings were high (91.7%). Participants reported looking forward to chat sessions and would recommend the chat to others. The vast majority reported that the chat helped them cope with their child's eating disorder and to implement FBT. Participants reported feeling that they could talk openly and honestly in sessions and had a sense of belonging to the group. Relatively few technical problems were reported, and the chat was rated as accessible, convenient and easy to use. Discussion Findings provide preliminary support for the utility of an online parent chat as an adjunct to FBT. Copyright © 2012 John Wiley & Sons, Ltd and Eating Disorders Association.